Non-shivering thermogenesis in four species of African mole-rats differing in their sociality - Luna, Facundo (2021)
Many mammalian species are adapted to living in burrows for most of their lives. Inhabiting such thermally stable environments may influence the variation on the species thermogenic capacity, particularly non-shivering thermogenesis (NST). African mole-rats (Bathyergidae) are subterranean rodents occurring in fynbos, grassland and wooded savannas across sub-Saharan Africa that vary in the complexity of their social systems, ranging from strictly solitary to highly social species. The presence and magnitude of NST are well known in social bathyergids, but no such data exist for their solitary counterparts. In this study, we quantified NST in three solitary mole-rat species represented by three distinct genera together with one social species. Our results showed that NST in all species is functional. Maximum metabolic rate after norepinephrine injection was equivalent to 269% of resting values in the social giant mole-rat Fukomys mechowii and 166%, 282% and 157% in the three solitary species: the silvery mole-rat Heliophobius argenteocinereus, the Cape mole-rat Georychus capensis and the Cape dune mole-rat Bathyergus suillus, respectively. To test our prediction that NST capacity is higher in solitary bathyergids, we combined our data with those available for other members of this family. In contrast to our prediction, NST did not differ between social and solitary bathyergids. Body mass, as the main factor, and minimum air temperature (Tmin), accounts for more than 80% of NST variation in bathyergid mole-rats.